PENGUATAN SUMBER DAYA MANUSIA PADA SEKTOR PERTANIAN WILAYAH BALI DI ERA PANDEMI COVID-19 - I Dewa Made Arik Permana Putra; Tiara Carina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
The impact of the COVID-19 pandemic has been experienced by Indonesia affecting various aspects of people's lives. Many sectors are affected by this pandemic, but the agricultural sector is a sector that is able to survive in the midst of this condition. This research aims to find out the possibility of strengthening human resources in the agricultural sector by shifting workers affected by COVID-19 to the agricultural sector. The method used is to use a literature study of the results of previous research and books and articles that raise themes and topics about the development of Covid-19 affect the human resources of the tourism and agriculture sector in the Bali region. Based on the results of the study, there is an increase in daily spikes in Covid-19 cases in Indonesia in 2020 which is quite significant. The results of the study also showed that layoffs in the Bali region also experienced the same thing, especially in 2020 many tourism workers were laid off from their companies. Human resource improvement solutions can be done by providing opportunities and opportunities for human resources who experience layoffs to work in the agricultural sector that requires a lot of labor. It is necessary to provide stimulus in the form of training through competency certification in agriculture, it is also necessary to be taught to use agricultural machinery to manage agricultural land to change the mindset of farmers for the lower classes and to provide these workers with urban farming training in order to grow food crops at home to meet their needs. food.